Comparison of Mathematics Learning Achievement in Students Admission Zoning and Non-zoning at Senior High School - Dwi Saviana Risqi Agustin; Yusuf Nalim (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This study aims to determine the effect of the acceptance of new students through the zoning system on mathematics learning achievement through the comparison of student achievement before going through the zoning system and through the zoning system. Quantitative research uses data on students' mathematics learning achievement scores. This study uses quantitative research to process data in the form of numbers. The data is in the form of learning achievement scores for student math. The dependent variable used is mathematics learning achievement. This study used 58 samples for students before going through zoning and 59 students through the zoning system. The analytical method used is the Mann-Whitney comparison of two unpaired samples. The results showed that the statistical value of 0.000 <0.10 with the average student admission before going through the zoning system was 82.00 and students admission through the zoning system was 78.63. Thus, the results of the study show that there is a significant difference between the mathematics learning achievement of students admission students before going through the zoning system and PPDB through the zoning system. Therefore students admission through a zoning system can affect students' mathematics learning achievement